(The Effect of Using Technology and Modern Techniques in Teaching Geography Subject on Academic Achievement of Grade 12 Students at Abdullah Bin Abad Al- Tamimi Basic Education School (10- 12 - Al Harasi, Saif bin Darwish bin Saeed; Al Samsami, Rashid bin Suleiman bin Rashid; Al Kindi, Mohammed bin Saeed bin Mohammed; Al Kharusi, Hussein bin Ali bin Talib (Journal of Educational and Psychological Sciences, 2018)
The present study aimed to investigate the effect of using modern technology in teaching geography and modern technology subject on academic achievement. The study population consisted of 70 grade 12 literary section students at Abdullah Bin Abad AL- Tamimi School (10- 12) and Aqeel bin Abi Talib School for Basic Education (5- 12). The sample consisted of a control group represented by 27 students from Aqeel bin Abi Talib Basic Education School while the experimental group was represented by 43 students from Abdullah bin Abad Basic Education School. The group equivalence was confirmed through a pretest. The control group was taught in the normal way while the experimental group was taught using modern technology، after which a post- test was conducted for the two groups. Results of the post- test showed that there were no statistically significant group differences at the level of (0،05). This might be attributed to the degree of difficulty of geography and new techniques. The study recommends that the preparation of geography subject be prepared more easily and flexibly.
Keywords: teaching; geography; modern technologies; academic achievement